Implementasi Manajemen Pengetahuan Islam di Sekolah Muhammadiyah - Mufti, Umam; Nur Fauzi, Hafidh; Perawironegoro, Djamaludin (Jurnal Tarbiyatuna, 2019)
Knowledge Management can be understood with a systematic step in managing intellectual assets / knowledge and various information from individuals and organizations to create excellence in competing for added value and innovation. Apart from that, knowledge is one of the agency's assets and can be a separate competitive advantage if it can be managed well. The current problem is the development of technology and the increasing competitiveness that occurs between educational institutions. If an educational institution does not have good knowledge management, of course, it will be left behind. Then good management is needed and is maximally applied in SD Muhammadiyah Trini Gamping Selman DIY. Implementation management takes into account two aspects, namely identification of knowledge and identification of structure and attention also found on the tacit and explicit factors as a pattern of developing knowledge management. If all of these factors are considered and applied correctly, superior schools that have good and superior management will emerge.